The psychosocial determinants of the intention to test for HIV among young men in KwaZulu-Natal province, South Africa. Issue 1 (2nd January 2021) - Manyaapelo, Thabang; Ruiter, Robert AC; Sifunda, Sibusiso; Nyembezi, Anam; van den Borne, Bart; Reddy, Priscilla
Abstract : Background: Voluntary counselling and testing is one of the effective prevention strategies against the HIV/AIDS epidemic. This study investigated the psychosocial determinants of the intention to be tested for HIV among young men in South Africa's KwaZulu-Natal province using the theory of planned behaviour as the guiding framework. Method: A facilitator-administered questionnaire was used to collect data among 350 isiZulu-speaking men between the ages of 18 and 35. Results: Results show that 24% reported ever having tested. Intention to test showed strong positive correlations with subjective norm to test ( r = 0.67), intention to use condoms ( r = 0.65), intention to reduce alcohol use ( r = 0.60), subjective norm to reduce alcohol use ( r = 0.54), and subjective norm to use condoms ( r = 0.51). For multiple regression, attitude, subjective norm and perceived behavioural control explained 43% of the variance in intention to test, with subjective norm and perceived behavioural control making significant unique contributions. An additional 12% of the variance was explained by intention to reduce alcohol and drug use, and use condoms. Conclusion: Behavioural interventions to encourage HIV testing among men should target normative and control beliefs but also other risky behaviours (e.g. alcohol abuse and condom use) as reductions in these behaviours appear to be positively associated with motivation to undergo HIV testing.